SOCIO-TECHNICAL DIMENSIONS OF THE DIGITAL DIVIDE IN DIABETES TECHNOLOGY: A SYSTEMATIC REVIEW OF INEQUITY IN CGM ADOPTION - Weronika Napierała; Karolina Magda Leszczyńska; Jeremi Leon Jasiński; Anna Krzysztofik; Karolina Krawczyk; Kamila Teresa Kańska; Aleksandra Maria Tomaszewska; Alicja Maria Mitan; Maciej Tomasz Wieczorek; Karolina Julia Hak (International Journal of Innovative Technologies in Social Science, 2026)
Background: Diabetes mellitus remains a significant global health burden. While the rapid advancement of diabetes technologies—such as Continuous Glucose Monitoring (CGM) and mobile health (mHealth) applications—has transformed clinical outcomes, it has also introduced a widening "digital divide."Objective: This review evaluates the impact of socioeconomic barriers on the adoption of modern diabetes technologies and discusses the implications for health equity through a socio-technical systems lens.Methodology: Following a systematic literature search, 20 high-impact articles published between 2021 and 2026 were analyzed. The selection includes systematic reviews, cohort studies, and mixed-methods research from diverse geographical contexts, including the United States and the United KingdomResults: The analysis identifies that financial barriers are compounded by deep-seated systemic failures. Even in universal healthcare models (e.g., the UK’s NHS), ethnic minorities and socioeconomically deprived populations are significantly less likely to be prescribed CGM technology [7]. Beyond cost, the review identifies "clinician implicit bias" [8, 14], lack of digital literacy in safety-net settings [13], and deficiencies in universal design for individuals with sensory disabilities [19] as primary obstacles. Furthermore, rural populations face distinct infrastructural hurdles that impede technology adoption [10, 15].Conclusion: Findings suggest that technological progress may paradoxically widen health disparities unless a "human-centered" and systems-based approach is adopted. Policy interventions must move beyond mere reimbursement to address clinician education, inclusive interface design, and infrastructural equity to ensure that innovation serves as a tool for reducing health inequalities.